PENINGKATAN KETERAMPILAN MENULIS TEKS TANGGAPAN MENGGUNAKAN MODEL FLIPPED CLASSROOM DENGAN MEDIA WORDWALL - Heavenlim, Natalia Rosi; Khairullah, Khairullah (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
Flipped classroom is a learning model used during hybrid learning during the co-19 pandemic, this provides a very significant paradigm shift because it provides a solution to learning with limited time. In addition, wordwall media which is widely used during online learning also provides a breath of fresh air in the world of education because it presents more interactive learning. The formulation of the problem in this study is how to plan, implement, and learn outcomes using the flipped classroom model with wordwall media. The method used in this research is descriptive in the form of classroom action research. The results of this study are the flipped classroom learning model with wordwall media for learning to write response texts that have been successful up to the second cycle, each cycle in the implementation of learning plans, implementation, and learning outcomes has increased significantly. The learning implementation plan experienced an increase of 19.59% between cycle I and cycle II. Implementation of learning has increased 35.29%. And learning outcomes have increased from only 24 students who complete to 35 students who complete. Based on this, the conclusion is that the flipped classroom learning model with wordwall media is able to improve students' writing response text skills.